Experimental measurement of H2(aq) solubility in hydrothermal fluids: Application to the Piccard hydrothermal field, Mid-Cayman Rise. (15th August 2020) - Scheuermann, Peter P.; Xing, Yanlu; Ding, Kang; Seyfried, William E.
Abstract: In mid-ocean ridge hydrothermal systems the fluid redox state is controlled by oxidation of ferrous iron in the host rock and generation of aqueous hydrogen, H2(aq). A quantitative interpretation of redox state requires conversion of H2(aq) concentrations to H2 fugacity, f H2 . Here we present the results of hydrothermal experiments that calibrate the f H2 -concentration relationship in saline hydrothermal fluids, YH2 -Cl . H2(aq) concentrations were measured between 400 and 500 °C, 210 and 510 bar, in both single-phase fluids and low-density vapors in the KCl-H2 O system. The assemblage hematite-magnetite was used to buffer f H2 . Values of YH2 -Cl are well above unity and decrease as temperature increases. Along isotherms YH2 -Cl decreases as the fluid density decreases. At 400 °C, 330 bar and 1000 mmol/kg KCl YH2 -Cl is 316 bar/molal and decreases to 4 bar/molal at 500 °C, 400 bar and 33 mmol/kg KCl. In combination with previous determination of H2 S(aq) solubility at hydrothermal conditions, the data presented here permit calculation of the redox conditions of natural vent systems. Redox conditions calculated for the basalt-hosted Piccard hydrothermal field suggest amphibolite facies mineral assemblages are present at depth, consistent with the extremely hot temperatures (>500 °C) inferred from analysis of other aspects of vent fluid chemistry (e.g., Cl and SiO2 ). Piccard may be the first location of active venting that records, through its composition, evidence for an alteration assemblage that had been previously observed only in fossilized submarine hydrothermal systems.